Study on the Self–Bearing Mechanism and Mechanical Properties of Gangue Slurry under Overburden Loading - Sixu Liu; Jianfei Xu; Nan Zhou; Yuzhe Zhang; Chaowei Dong; Zhuo Lv (Applied Sciences, 2024)
The mining of coal resources is accompanied by a large amount of solid waste such as gangue, which seriously affects the ecological environment. The gangue grouting backfilling technique can achieve the dual goals of gangue disposal and surface deformation control by injecting gangue slurry into the underground. The bearing mechanical characteristics of gangue slurry directly affect the surface deformation control effect of the grouting backfilling technique. In this study, a loading simulation system of grouting backfilling materials was designed, uniaxial confined compression tests were conducted, and the self–bearing mechanism of large particle–sized gangue slurry with different fluidities under instantaneous and creep loading modes was investigated. Additionally, the mechanical characteristics of the compacted body (i.e., the gangue slurry after creep loading) were analyzed. The results indicate that the self–bearing process of gangue slurry can be divided into three stages: the rapid compression and drainage stage, the pore compaction and water bleeding stage, and the particle crushing and elastic–plastic deformation stage. The uniaxial compressive stress–strain curve of a compacted body can be classified into four stages: elastic stage, yield stage, reinforcement stage, and crushing stage, and the strength of the compacted body is affected by the loading time and fluidity of the slurry. When the slurry with a fluidity of 240 mm is subjected to constant pressure for 3 h, the compressive strength of the slurry reaches the maximum value of 4.98 MPa, and 13.1% stress damage occurs when the constant pressure reaches 4 h. This research provides a theoretical basis for the improvement of the proportion and bearing characteristics of gangue grouting materials.